A 128 Gb/s PAM4 Silicon Microring Modulator With Integrated Thermo-Optic Resonance Tuning - Jie Sun; Kumar, Ranjeet; Sakib, Meer; Driscoll, Jeffrey B.; Jayatilleka, Hasitha; Haisheng Rong (Journal of lightwave technology, 2019)
We report the first demonstration of a silicon photonic microring modulator with modulation data rate up to 128 Gb/s (64 Gbaud PAM4). The microring modulator exhibits an electro-optic phase efficiency of V π · L = 0.52 V·cm, an electro-optic bandwidth of 50 GHz, and a measured transmitter dispersion eye closure quaternary of 3.0 dB at this data rate. In addition, the resonant wavelength of the microring modulator can be tuned across a full free spectral range using an integrated heater with a thermo-optic phase efficiency of 19.5 mW/π-phase shift.